Fātimah al-Fihrī and religious fraternity in al-Qarawiyyin University: A Case Study - Souad, Merah; Ramdane, Tahraoui; Khan, Mariya Seemin (2016)
The status of Muslim women is a sensitive issue which has always provoked a lot of controversy.  A commonly notion among, feminists, scholar-activists and academics, western and non-western is the claim that Muslim women in most of the Muslim world are oppressed and systematically suffer from discriminatory patriarchal gender system and male domination culture.  Contrary to that claim, conservative Muslim activists and religious scholars deny any sort of mal-treatment and oppression that Muslim women received. Interestingly, most of the literature related to this issue lacks female representation.